Предмет: Алгебра,
автор: MrBlackMan
Решите уравнение ((x : 2 − 3) : 2 − 1) : 2 − 4 = 3
Ответы
Автор ответа:
0
((x : 2 − 3) : 2 − 1) : 2 − 4 = 3
сначала делаем не в скобках и слева направо, а справа налево
будет понятней и гораздо легче решать
((x : 2 − 3) : 2 − 1) : 2 = 3+4
((x : 2 − 3) : 2 − 1) : 2 = 7
(x : 2 − 3) : 2 − 1 = 7 * 2
(x : 2 − 3) : 2 = 14 + 1
x : 2 − 3 = 15 * 2
x : 2 = 30+3
x=33*2
x=66
сначала делаем не в скобках и слева направо, а справа налево
будет понятней и гораздо легче решать
((x : 2 − 3) : 2 − 1) : 2 = 3+4
((x : 2 − 3) : 2 − 1) : 2 = 7
(x : 2 − 3) : 2 − 1 = 7 * 2
(x : 2 − 3) : 2 = 14 + 1
x : 2 − 3 = 15 * 2
x : 2 = 30+3
x=33*2
x=66
Похожие вопросы
Предмет: Математика,
автор: gribanovtimofij34
Предмет: Математика,
автор: shornoevzhalsan
Предмет: Литература,
автор: Аноним
Предмет: История,
автор: ЯнОчКаКрИвОрУчКо
Предмет: Математика,
автор: andreymotorny